Establishing norms for functional translations from Portuguese to English: The case of academic calls for papers - Tack Erten, Sonja (The Journal of Specialised Translation, 2012)
There is growing recognition that the greater the translator's awareness of how specific genres operate at both the cultural and textual levels in particular language pairs, the more likely the resulting translation is to achieve the goal of functional equivalence. This study uses a small comparable corpus to investigate the similarities and differences in the genre conventions of academic calls for papers (CFPs) written in American English and Brazilian Portuguese. The schematic structure and textual functions of CFPs are identified, and Halliday's systemic functional grammar is used to sketch out the broad common features of this genre. Significant differences at the micro-pragmatic level of discourse are then described, and several practical translation strategies are suggested for translators working from Portuguese into English. The overall aim is to encourage translators to make a series of choices that will achieve an overall effect which is highly appropriate to the pragmatic norms of the target text.